Mengukur Pencapaian Tujuan Pembangunan Berkelanjutan di Pedesaan: Studi Kasus Desa Sukamantri di Kabupaten Bogor, Jawa Barat, Indonesia - Sjaf, Sofyan; Kaswanto, Kaswanto; Kuniawati Hidayat, Nia; Ardinal Barlan, Zessy; Elson, La; Sampean, Sampean; Firda F Gunadi, Hanifa (Sodality: Jurnal Sosiologi Pedesaan, 2021)
A village is an arena for sustainable development where economic, social, cultural, environmental and political interactions occur. It has a strategic meaning for the successful achievement of the 17 indicators of Sustainable Development Goals (SDGs). However, villages have limitations in providing data and indicators to measure the achievement of SDGs based on RW. The aims of this study are to provide Precision Village Data (DDP) and use it to measure and analyze the achievement indicators of 16 out of 17 village SDGs. One of SDGs 14, namely the marine ecosystem is not measured because the research location is a terrestrial village with an altitude of 423-902 m ASL. The use of DDP in the research location with normalization and aggregation methods based on arithmetic averages made this study successful in calculating the scores of each village SDGs. Then the results of the analysis of the village DDP and SDGs were combined with spatial mapping. The results showed that the SDGs in Sukamantri Village cumulatively achieved quite good results. A total of 3 SDGs was classified as very good, 4 SDGs were classified as good, 3 SDGs were classified as good enough, 5 SDGs were lacking, and 2 SDGs were poorest. Referring to the SDGs index calculation for Sukamantri Village, the environmental pillar has the highest score and is on average very good. However, the social and economic pillars are in the poor category, the law and governance pillars are in the poorest category. This means that sustainable development in Sukamantri Village has not been achieved. The natural wealth in Sukamantri Village has not been managed to achieve the fulfillment of basic human rights that are of a just and equal quality, for the well-being of the villagers and the realization of inclusive and quality economic growth.